A study on the satisfaction of business administration students at a public university (Research, Society and Development, 2021)
The main purpose of this article was to identify and analyze the main factors that influence the satisfaction of Management students at a public university, located in the west of Minas Gerais with the institution, the course and the factors related to the development opportunity. A descriptive case study with a quantitative approach was carried out. The universe of the research was the 150 students of the Administration course and the sample was defined by accessibility and composed of the 80 students who were present in the classroom on the day of the research. The questionnaire was used as a data collection instrument. The work showed that the students of the Administration course were mostly female, under 25 years of age, were already inserted in the job market and did not receive any financial aid from the institution. It was also found that the students were satisfied with the institution and the course, with the main factors generating this satisfaction being the institution's infrastructure, the services offered by the library, the relationship with teachers and the adequacy and relevance of the contents of the subjects of the course. As for the factors related to development opportunities, there was no factor that would generate satisfaction for most of the students surveyed.